Efektivitas Penggunaan Aplikasi Wordwall Dalam Pembelajaran Daring (Online) Muatan PKN Pada Materi Hak Dan Kewajiban Terhadap Tumbuhan Kelas 4 Di SDN 16 Gunung Tuleh Pasaman Barat Sumatera Barat - Nurhamida, Nurhamida; Putri, Fanny Mestyana (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to overcome the boredom of students during distance learning (PJJ) by utilizing the internet network, as well as information and communication technology (ICT). Teachers must package learning into a game. “Games are played primarily for entertainment, fun, but can also function as a means of training, education, and simulation. One of the web-based applications that are easy to use is wordwall. Wordwall can be used to create educational game learning media such as quizzes, matchmaking, pairing, anagrams, word randomization, word search, grouping, and so on. With this application, it is hoped that it will make it easier for students to understand a learning material using online so that the motivation in learning is increasing. From the results of the closing activity for PKN content, the material on rights and obligations to plants in its use of wordwall media, the closing activity was affective, from 20 students it was obtained that 15 people got a complete score, 5 people got an incomplete score on the first test and 17 people got a score completed and 3 people who have not been completed for test II. In the use of Wordwall media, it can be seen that the results of students' learning achievements have been running effectively with students' mastery on the first test of 70% and the results of the second test of 85% (up 15%).